Zooplankton diversity in selected coastal waters of area in mandaithivu, island jaffna, sri lanka. - Jananan, T.; Sivakumar, P. (Proceedings of Jaffna Science, Association Vol 26 -No 01, 2019)
Zooplanktons are floating and drifting with limited power of locomotion. They occupy an intermediate position between autotrophs and carnivores in the food web. The presence and dominance of zooplankton species plays an important role in the functioning of aquatic ecosystem. The present investigation was carried out to identify the zooplanktons species and diversityin Mandaithivu coastal waters. Samples were collected from October 2017 to March 2018 in selected coastal waters, Jaffna between 6am-10am. Collected Zooplanktons were identified using standard keys according to the morphological features. Eight species of zooplanktons, Copepod, Ostracod, Daphnia, Foraminifera, Fish larvae, Veliger larvae of Mollusc, nauplius and shrimp like organisms were identified. Nauplius and Daphnia sp were observed in highest amountthan fish larvae, veliger larvae and ostracods whereas foraminifera were the least. During the study period, Copepods was recorded as the dominant species in Mandaithivu coastal waters.
Keywords: Zooplankton; Mandaithivu